2019
DOI: 10.1186/s13046-019-1334-5
|View full text |Cite
|
Sign up to set email alerts
|

TET1-mediated DNA hydroxymethylation activates inhibitors of the Wnt/β-catenin signaling pathway to suppress EMT in pancreatic tumor cells

Abstract: Background Ten-eleven translocation 1 (TET1) is a dioxygenase that converts 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC) to induce DNA demethylation. TET1 has been reported to be absent in cancers, and to influence various oncogenes and anti-oncogenes. However the function of TET1 in pancreatic tumor remains poorly understood. In this study, we investigated the role of TET1 in the progression of pancreatic tumor and its mechanism of tumor suppression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…TET1, as DNA demethylase, is thought to be related to tumor metastasis [ 280 ]. TET1, as DNA demethylase, is thought to be associated with tumor metastasis, and hypoxia increases the expression of TET1 in a HIF-1α-dependent manner [ 281 , 282 ]. Because the binding of HIF-1α to HRE of target genes depends on the methylation level of CpG, TET1 can regulate the HIF-1α target genes by regulating the methylation state of HRE [ 278 ].…”
Section: Role Of Hif-α In Metastasis Through Epigenetic Regulationmentioning
confidence: 99%
“…TET1, as DNA demethylase, is thought to be related to tumor metastasis [ 280 ]. TET1, as DNA demethylase, is thought to be associated with tumor metastasis, and hypoxia increases the expression of TET1 in a HIF-1α-dependent manner [ 281 , 282 ]. Because the binding of HIF-1α to HRE of target genes depends on the methylation level of CpG, TET1 can regulate the HIF-1α target genes by regulating the methylation state of HRE [ 278 ].…”
Section: Role Of Hif-α In Metastasis Through Epigenetic Regulationmentioning
confidence: 99%
“…Other novel (potential) biomarkers in cervical cancer that undergo hydroxymethylation include ACTG1, SALL3, DNAJA3, SERPINB6, CDC14B, and CALN1 (Wang et al, 2019). Wu et al (2019) have demonstrated the downregulation of TET1 and 5-hmC in pancreatic tissues and cell lines. Pancreatic cancer patients with high TET1 levels exhibit longer overall survival than patients with low levels of TET1.…”
Section: Aberrant Dna Hydroxymethylation In Cervical and Other Cancersmentioning
confidence: 99%
“…Therefore, TET1 can suppress pancreatic tumor development by inhibiting proliferation and metastasis. This is achieved via Wnt signaling where TET1 binds and demethylates the promoter of the secreted frizzled-related protein 2 (SFRP2) to activate SFRP2 transcription (Wu et al, 2019). Interestingly, TET1 can suppress colon cancer, wherein TET1 binds to the promoter of DKK and inhibits Wnt signaling to maintain the hypomethylated state (Neri et al, 2015).…”
Section: Aberrant Dna Hydroxymethylation In Cervical and Other Cancersmentioning
confidence: 99%
“…10 As regard to Wnt/β-catenin, it also belongs to a classical signaling pathway in the pathological process of tumor, which is over-expressed in tumor cells and has some certain effects on their proliferation and apoptosis. 11 PRRX1 was supposed to be a potential target site for miR-330-3p through online biological prediction software (http://www.targetscan.org/vert_72/). Based on previous research, we speculated that miR-330-3p could affect the biological function of GC cells by targeting Wnt/β-catenin signaling pathway mediated by PRRX1, and thus the following research was conducted.…”
Section: Introductionmentioning
confidence: 99%